Combination of vaporized ethyl pyruvate and non-thermal atmospheric pressure plasma for the inactivation of bacteria on lettuce surfaces - Ermis, Ertan; Yagci, Menice Ogurlu; Durak, Muhammed Zeki (ELSEVIER SCI LTD, 2021)
The effect of vaporized ethyl pyruvate (EP) and atmospheric pressure plasma (APP) treatments on the inactivation of total viable counts of bacteria on fresh lettuce leaves samples after treatment and during storage (1 and 3 days) at 6 and 25 degrees C was studied. For this purpose, freshly grown B. cereus and Escherichia coli were inoculated on the lettuce leaves prior to treatments. Combination of EP (at a concentration of around 10 mu L dm-3) with APP was more effective on inactivation of bacteria when compared to EP and APP treatments separately, reducing the total viable counts nearly 5 CFU cm-2 compared to control. The use of EP and APP together led to around 2.5 more log (CFU cm-2) reductions when compared to the sole use of EP and APP separately. B. cereus cells were almost three times more susceptible to APP treatment than E. coli. Growth inhibition increased after storing the treated samples at 25 degrees C by around 2.5 and 1.5 logs for E. coli and B. cereus, respectively, compared to 6 degrees C. APP treatment time (30 and 60 s) and storage time (1 and 3 days) did not significantly affect the inactivation levels. E. coli was more effectively inactivated after EP + O2 treatment followed by storage at 25 degrees C. The highest level of inactivation was noted as nearly 5 log reductions. Slight differences in the peak intensities of FTIR spectra of treated lettuce samples were observed compared to control, indicating slight modifications on the chemical structure on the lettuce leaves. Industrial relevance: The microbial load influences the quality, safety, and shelf-life of fresh produce such as lettuce. Current decontamination techniques may cause some unwanted effects such as odor, discoloration, and decreased nutritional value. This study shows that the use of the APP-EP hurdle represents a promising strategy to improve the decontamination efficiency and hence, enhance the shelf-life of freshly cut vegetables. The data obtained contribute to a better understanding of APP-EP-induced effects on the quality and shelf-life of fresh-cut lettuce and provide a scientific basis for industrial implementation.
Keywords: Atmospheric cold plasma; Ethyl pyruvate; Shelf-life; Non-thermal inactivation; Escherichia coli; B; cereus; ESCHERICHIA-COLI; FRESH PRODUCE; BACILLUS-CEREUS; DECONTAMINATION; QUALITY; Food Science & Technology